2005
DOI: 10.1038/sj.leu.2403797
|View full text |Cite
|
Sign up to set email alerts
|

What have we learnt from mouse models of NPM-ALK-induced lymphomagenesis?

Abstract: The nucleophosmin-anaplastic lymphoma kinase (NPM-ALK) is generated as a t(2;5) chromosomal breakpoint product, typically in CD30 þ anaplastic large cell lymphomas. Activation of the NPM-ALK tyrosine kinase by NPM dimerisation causes autophosphorylation at multiple tyrosine residues and the consequent recruitment of a 'signalosome' that couples the fusion protein to pathways regulating mitogenesis and apoptosis. This review focuses on recent advances in our understanding of the transforming signals induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 58 publications
3
25
0
Order By: Relevance
“…In 2003, a mouse model was generated in which the expression of NPM-ALK, under the control of the CD4 promoter (Chiarle et al 2003), showed the spontaneous development of T-cell lymphomas and/or plasmacytomas, confirming the lymphomagenic role of NPM-ALK, providing a valuable tool for the study of ALCL. These findings were then confirmed using additional mouse models (Turner & Alexander 2005).…”
Section: Alk Expression In Hematological Disorderssupporting
confidence: 65%
“…In 2003, a mouse model was generated in which the expression of NPM-ALK, under the control of the CD4 promoter (Chiarle et al 2003), showed the spontaneous development of T-cell lymphomas and/or plasmacytomas, confirming the lymphomagenic role of NPM-ALK, providing a valuable tool for the study of ALCL. These findings were then confirmed using additional mouse models (Turner & Alexander 2005).…”
Section: Alk Expression In Hematological Disorderssupporting
confidence: 65%
“…Approximately 50-60% of cases of ALCL are associated with the t(2;5;)(p23;q35) chromosomal translocation, which generates a hybrid gene consisting of the intracellular domain of the ALK tyrosine kinase receptor juxtaposed with NPM. The resulting fusion protein, NPM-ALK has constitutive tyrosine kinase activity and has been shown to transform various hematopoietic cell types in vitro and support tumor formation in vivo (1,6). Other less frequent ALK fusion partners, e.g., tropomyosin-3 and clathrin heavy chain, have also been identified in ALCL as well as in CD30-negative diffuse large-cell lymphoma (1,2,7,8).…”
mentioning
confidence: 99%
“…32 A direct role for NPM-ALK in cellular transformation has been shown both in vitro and in vivo, and such studies have shed light on the mechanisms of malignant transformation by this oncoprotein. 33,34 These mechanisms include activation of several downstream signal-transduction pathways, which regulate cell survival, proliferation, migration and, more recently, hypoxia. 20,24 Although hypoxia has been reported to upregulate HIF-1a and VEGF in ALK-positive (ALK þ ) ALCL, 20 so far no studies have implicated it in angiogenesis in ALK tumor development.…”
Section: Discussionmentioning
confidence: 99%